A reliable fossa ovalis impedance mapping for safer transseptal puncture: A new vision beyond voltage. (24th October 2021) - Pentimalli, Francesco; Cornara, Stefano; Astuti, Matteo; Bacino, Luca; Somaschini, Alberto; Mazzucchi, Paolo; Buscaglia, Elisa; Cordone, Stefano; Ghione, Matteo; Errigo, Daniele; Bellone, Pietro
Abstract: Introduction: Transseptal puncture (TSP) is widely used in clinical practice but is negatively affected by a nonneglectable rate of complications and X‐ray exposure. To address these problems, we investigated whether or not impedance mapping could correctly identify fossa ovalis (FO) and safely guide TSP. Methods and Results: Electroanatomic mapping was performed with CARTO 3 system version 7 and a ThermoCool® SmartTouch® mapping catheter was employed. In each patient, an impedance map and a bipolar voltage map of the whole interatrial septum were collected, acquiring at least 150 points with a contact force ≥2 g and using the pattern matching filter. Thirty‐five patients were enrolled. A low impedance area was clearly identified in 34 of them. In 30 patients (88%), the FO was located in the low impedance area. The map was obtained in sinus rhythm in 17 cases (50%); in 15 of these (88%), the TSP site, the patent foramen ovale, or the FO tenting area fell inside the low impedance area. The same numbers were observed when mapping during atrial fibrillation. Conclusion: To the best of our knowledge, this is the first study that provides the reliability and reproducibility of impedance mapping in identifying FO, an affordable and feasible tool that could be potentially introduced into clinical practice.